STUDY LITERATURE TENTANG PEMBERIAN MINUMAN KUNYIT ASAM TERHADAP TINGKAT NYERI MENSTRUASI PADA REMAJA PUTRI - Tiara Widiatami; Melyana Nurul Widyawati; Admini Admini (JURNAL KEBIDANAN, 2018)
Menstrual pain or dysmenorrhea is a gynecological complaint caused by an imbalance of the progesterone hormone in the blood that causes pain and most often occurs in women. Women who experience menstrual pain usually produce prostaglandin 10 times more than women who do not experience menstrual pain. This prostaglandin causes an increase in uterine contractions that causes menstrual pain.Research purposes: to identify literature related to acidic turmeric drinks to menstrual pain levels.               The type of literature study conducted is using analytical metadata using literature (literature review) that can explain the benefits of acid turmeric drinks to reduce pain levels during menstruation.               Menstrual pain is abdominal pain that comes from uterine cramps that occurs during menstruation. Usually occurs at the onset of menstruation and lasts several hours to several days until it reaches the peak of pain. Menstrual pain is the most common problem in adolescent and adult women, but is a different condition for many women who influence health-related quality of life. Menstrual pain, the fact that women cannot act normally can have an economic impact, because it relates to expenditures spent on purchasing, and medical care. To reduce prices on dysmenorrhea respondents, what we did was to give acidic turmeric drinks to respondents who were conceived during menstruation. Acidic turmeric drinks are drinks that are processed with the main ingredients of turmeric and acid. Naturally turmeric is believed to have active ingredients that can be used as analgesic, antipyretic and anti-inflammatory, so it is also acidic (tamarind) which has active ingredients as anti-inflammatory, antipyretic and sedative.